Combining ultrasonic guided wave and low-frequency electromagnetic technology for defect detection in high-temperature Cr–Ni alloy furnace tubes - Du, Chenyang; Li, Xiaowei; Liu, Chang; Song, Ce; Yuan, Jun; Xin, Yanchao (Scientific reports, 2023)
Cracking furnaces, operating under high temperatures and in a hydrocarbon medium, subject their tubes to complex stresses such as internal pressure, self-weight, fatigue, and thermal shock during start-up and shutdown. As a result, these furnace tubes frequently experience failures characterized by cracks and corrosion perforation. The high-temperature environment, constantly evolving structure of the tubes, and the close arrangement of the cracks within the tube box hinder detecting the cracks using conventional single-detection methods is challenging. This paper breaks through the limitations of the traditional single detection method and studies the effectiveness of the combination of ultrasonic-guided wave and low-frequency electromagnetic detection methods. The experiment was carried out by deliberately making cracks and thinning defects caused by corrosion on the cracking furnace tube of Cr35Ni45Nb after two years of service. The experimental results show that the ultrasonic guided wave detection technology can quickly detect the defects running through the whole furnace tube and effectively identify the manufacturing defects. On the other hand, low-frequency electromagnetic detection makes it possible to scan suspicious local defects and make qualitative and quantitative analyses of defect signals. The combination of ultrasonic guided wave and low-frequency electromagnetic detection can realize the rapid location and comprehensive qualitative and quantitative analysis of furnace tube defects, thus making up for the defects missed detection caused by the lack of effectiveness of single detection and the resulting safety problems. The research results have great popularization value in practical engineering applications.